The Ubiquity of Humanity and Textuality in Human Experience - Daihyun Chung (Humanities, 2015)
The so-called “crisis of the humanities” can be understood in terms of an asymmetry between the natural and social sciences on the one hand and the humanities on the other. While the sciences approach topics related to human experience in quantificational or experimental terms, the humanities turn to ancient, canonical, and other texts in the search for truths about human experience. As each approach has its own unique limitations, it is desirable to overcome or remove the asymmetry between them. The present article seeks to do just that by advancing and defending the following two claims: (a) that humanity is ubiquitous wherever language is used; and (b) that anything that can be experienced by humans is in need of an interpretation. Two arguments are presented in support of these claims. The first argument concerns the nature of questions, which are one of the fundamental marks or manifestations of human language. All questions are ultimately attempts to find meanings or interpretations of what is presented. As such, in questioning phenomena, one seeks to transcend the negative space or oppression of imposed structures; in doing so, one reveals one’s humanity. Second, all phenomena are textual in nature: that which astrophysicists find in distant galaxies or which cognitive neuroscientists find in the structures of the human brain are no less in need of interpretation than the dialogues of Plato or the poems of Homer. Texts are ubiquitous. The implications of these two arguments are identified and discussed in this article. In particular, it is argued that the ubiquity of humanity and textuality points to a view of human nature that is neither individualistic nor collectivist but rather integrational in suggesting that the realization of oneself is inseparable from the realization of others.